2002
DOI: 10.1590/s0100-204x2002000300018
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização espectral de Paspalum notatum em diferentes níveis de adubação nitrogenada

Abstract: Resumo As propriedades espectrais da vegetação podem ser utilizadas para o monitoramento das condições de crescimento da vegetação ao longo do ano, assim como a estimativa da produtividade das espécies, por meio de técnicas de sensoriamento remoto. Para tanto, é necessário, primeiramente, caracterizar espectralmente as espécies que compõem a vegetação de um ecossistema. O objetivo deste trabalho foi caracterizar a reflectância do Paspalum notatum Flügge var. notatum crescendo em diferentes níveis de adubação n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
2
1
0
2
Order By: Relevance
“…Similar results were observed by Backes et al (2010), who reported an increasing linear effect on the leaf + stem dry phytomass as a function of the dose of sewage sludge (0, 100, 200, 300, and 400 kg ha -1 N, delivered in a single application) in an area of emerald Zoysia production, and by Fonseca et al (2002), who observed that the control (absence of N) produced the smallest amount of total (stem + leaves) and green (only leaves) dry matter compared to the other treatments (200 and 400 kg ha -1 N, delivered in a single application, using ammonium sulfate as the source) in a study on bahiagrass.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results were observed by Backes et al (2010), who reported an increasing linear effect on the leaf + stem dry phytomass as a function of the dose of sewage sludge (0, 100, 200, 300, and 400 kg ha -1 N, delivered in a single application) in an area of emerald Zoysia production, and by Fonseca et al (2002), who observed that the control (absence of N) produced the smallest amount of total (stem + leaves) and green (only leaves) dry matter compared to the other treatments (200 and 400 kg ha -1 N, delivered in a single application, using ammonium sulfate as the source) in a study on bahiagrass.…”
Section: Resultssupporting
confidence: 85%
“…The results from this study confirm the N effect on plant shoot growth and the association between N fertilization doses and plant dry matter production (OLIVEIRA et al, 2010;FONSECA et al, 2002). However, a greater amount of dry matter is not a desirable result for lawns with ornamental purposes because it increases the demands for a greater mowing frequency to maintain the aesthetics (AMARAL; CASTILHO, 2012), thereby increasing the maintenance costs.…”
Section: Resultssupporting
confidence: 75%
“…Planaltina (Figure 3). The study shows that the spectral response alters with the variation of the biomass (FONSECA et al, 2002), because chlorophyll increases when N is applied to the plant. Therefore, the absorption of radiation in the region of the visible spectrum is greater, making NDVI to increase (READ et al, 2003).…”
Section: Resultsmentioning
confidence: 97%
“…A avaliação das diferenças dos níveis de nutrientes das plantas pode ser detectada por meio de sensores remotos. Diferenças nos níveis de nitrogênio das plantas, devido à adubação, já foram enfoques em vários trabalhos (JENSEN et al, 1990;FERNÁNDEZ et al, 1994;FONSECA et al, 2002).…”
Section: 37423/210403908unclassified